Alternative to peat for Agaricus brasiliensis yield - Colauto, Nelson Barros; Silveira, Adriano Reis da [UNESP]; Eira, Augusto Ferreira da [UNESP]; Linde, Giani Andrea (Elsevier, 2010)
Casing layer is one of the most important components of Agaricus spp. production and it directly affects mushroom productivity, size and mass. The aim of this study was to evaluate potential raw materials as a casing layer and their effect on Agaricus brasiliensis productivity. Raw materials from Brazil with potential use were selected and characterized, and the most promising ones were tested as casing layers for mushroom yield. Evaluated raw materials included lime schist, vermiculite, eucalyptus sawdust, sand, São Paulo peat, Santa Catarina peat, subsoil and charcoal. Particle size, porosity and water absorption in relation to mushroom yield for casing layers were determined. Lime schist, an alternate casing layer to peat, is presented and the effects of the casing layer on the mushroom yield are discussed. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Agaricus blazei; Biological efficiency; Casing layer; Lime schist; Productivity; Agaricus; Agaricus brasiliensis; Charcoal; Clay minerals; Lime; Soils; Water absorption; Peat; calcium oxide; charcoal; peat; vermiculite; absorption; crop production; crop yield; lime; mushroom; particle size; porosity; schist; Brazil; controlled study; fungal reproduction; nonhuman; plant yield; priority journal; productivity; sand; sawdust; species cultivation; water absorption; Soil; South America; Basidiomycota; Eucalyptus